The role of orbital transformations in coupled-pair functionals - Kollmar, Christian; Heßelmann, Andreas (Theoretical Chemistry Accounts, 2010)
The replacement of single excitations by orbital transformations in coupled-pair functionals derived from a single double configuration interaction approach is discussed. It is demonstrated that this modification leads to considerably improved density matrices and better agreement with results from coupled cluster singles doubles calculations taken as a reference. A comparison between the variationally optimized orbitals and the Brueckner orbitals shows that these two sets of orbitals are different.
EAM Import::2019-03-12